Design, Implementation and Evaluation of a Systematic Review Course for Medical Students - Mehrnoosh Khoshnoodifar; Moein Zangiabadian; Mehran Ilaghi (Kerman University of Medical Sciences, 2023)
Background: Teaching research skills to medical students is an essential component of modern medical education curricula. Despite the students' need and enthusiasm for practical research courses, there is a lack of basic training, particularly on secondary research types.Objectives: In this study, we aimed to design, implement and evaluate a systematic review training course for medical students.Methods: This was a pretest-posttest study conducted among medical students of Shahid Beheshti University of Medical Sciences (SBMU) in Iran.  A total of 78 medical students were screened for eligibility based on their lack of previous systematic review publication experience and 30 individuals were ultimately enrolled to participate in the training course. A pre-test consisting of 20 multiple-choice questions was administered to the students. Following the ADDIE instructional design model, the training course was conducted in 12 sessions using a blended approach (in-person, synchronous online, and asynchronous sessions). At the end of the course, the evaluation of student satisfaction, knowledge, and skills was performed based on the Kirkpatrick model.Results: Out of the 30 participating students, 27 successfully completed the course and took part in the post-test. Among them, 23 individuals expressed 100% satisfaction with the course implementation. Comparison of pre-test and post-test scores indicated a significant improvement in participants' theoretical knowledge (p-value<0.001). The most pronounced increase in the knowledge level was observed in clerkship students and interns. Asynchronous online teaching was significantly more effective than in-person and synchronous online methods. At the end of the course, eight participants tested their practical skills by successfully registering a systematic review study protocol on the International Prospective Register of Systematic Reviews (PROSPERO) website.Conclusion: Overall, this study underscores the value of organizing research workshops focused on systematic review methodology as an effective means to enhance the knowledge of medical students in the realm of high-quality evidence-based research methods.